Analysis of Company Valuation Based on Tobin's Q Model in Industrial Sector Companies on the Indonesia Stock Exchange - sriwahyuni (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
The industrial sector on the Indonesia Stock Exchange experienced significant challenges with fluctuating contributions to the JCI, showing an increase in the early period but declining substantially in recent years. This study aims to analyze the company value of industrial sector issuers on the Indonesia Stock Exchange using the Tobin's Q model for the period of four years. The research employs a quantitative descriptive approach with industrial sector companies selected through purposive sampling technique. Data was collected through financial statement documentation and analyzed using the Tobin's Q ratio to classify companies based on their market valuation conditions. The results reveal that the majority of companies have a Tobin's Q value below one, indicating that stock market values are lower than the book value of assets. Only a small portion of companies fall into the overvalued category. This study concludes that most industrial sector companies on the IDX have not optimally managed their assets and require improved asset management efficiency to create added value for shareholders. The findings suggest significant room for improvement in asset utilization within Indonesia's industrial sector.